Mutations in osteoprotegerin account for the CCAL1 locus in calcium pyrophosphate deposition disease. Issue 6 (June 2018) - Williams, C.J.; Qazi, U.; Bernstein, M.; Charniak, A.; Gohr, C.; Mitton-Fitzgerald, E.; Ortiz, A.; Cardinal, L.; Kaell, A.T.; Rosenthal, A.K.
Summary: Objective: Mutations on chromosomes 5p (CCAL2) and 8q (CCAL1) have been linked to familial forms of calcium pyrophosphate deposition disease (CPDD). Mutations in the ANKH gene account for CCAL2, but the identity of CCAL1 has been elusive. Recently, a single Dutch kindred with a mutation in the Tumor Necrosis Factor Receptor Super Family member 11B (TNFRSF11B) gene coding for osteoprotegerin (OPG) was described as a gain-of-function mutation. Affected family members had premature generalized osteoarthritis (PGOA) and CPDD. As the TNFRSF11B gene is on 8q, we sought additional evidence that TNFRSF11B was CCAL1, and investigated potential disease mechanisms. Design: DNA from two novel PGOA/CPDD families was screened for sequence variants in the TNFRSF11B gene. Mutations were verified by genotype analysis of affected and unaffected family members. We also investigated effects of normal and mutant OPG on regulators of CPP crystal formation in porcine cartilage. Results: The identical TNFRSF11B mutation described in the Dutch family was present in two novel PGOA/CPDD families. ANKH was normal in affected patient fibroblasts. Exogenous OPG did not alter ANKH mRNA or protein levels, affect translocation of ANKH to the membrane, nor increase [pyrophosphate (PPi)] or other key regulators of CPDD. Conclusion: We have firmly established the identity of CCAL1 as TNFRSF11B (OPG). Our findings suggest that this mutation produces disease in an ANKH-independent manner via novel mechanisms not primarily targeting cartilage. This work rationalizes further investigation of OPG pathway components as potential druggable targets for CPDD.